2014
DOI: 10.1002/anie.201409579
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids as Precursors for Efficient Mesoporous Iron‐Nitrogen‐Doped Oxygen Reduction Electrocatalysts

Abstract: A ferrocene-based ionic liquid (Fe-IL) is used as a metal-containing feedstock with a nitrogen-enriched ionic liquid (N-IL) as a compatible nitrogen content modulator to prepare a novel type of non-precious-metal-nitrogen-carbon (M-N-C) catalysts, which feature ordered mesoporous structure consisting of uniform iron oxide nanoparticles embedded into N-enriched carbons. The catalyst Fe(10) @NOMC exhibits comparable catalytic activity but superior long-term stability to 20 wt % Pt/C for ORR with four-electron tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(81 citation statements)
references
References 55 publications
0
81
0
Order By: Relevance
“…As a result, P(Co)-C Adv. [ 129,133,200,219 ] Lefevre et al [ 200 ] illustrated that ORR activity of Fe-N-C with ferrous acetate, phenanthroline and carbon support serving as precursors correlates with nominal Fe content as well as Nafi on-to-catalyst ratio (NCR), with 1 wt% Fe and ≈1.5 of NCR peaking the activity, which was also confi rmed in their ensuing report. 2016, 6, 1600458 www.MaterialsViews.com www.advenergymat.de wileyonlinelibrary.com exhibited much better ORR performances relative to P-C in terms of diffusion-limited current density, onset/half-wave potential and H 2 O 2 yields.…”
Section: Effect Of Transition Metals Acid Leaching and Second Pyrolymentioning
confidence: 66%
See 1 more Smart Citation
“…As a result, P(Co)-C Adv. [ 129,133,200,219 ] Lefevre et al [ 200 ] illustrated that ORR activity of Fe-N-C with ferrous acetate, phenanthroline and carbon support serving as precursors correlates with nominal Fe content as well as Nafi on-to-catalyst ratio (NCR), with 1 wt% Fe and ≈1.5 of NCR peaking the activity, which was also confi rmed in their ensuing report. 2016, 6, 1600458 www.MaterialsViews.com www.advenergymat.de wileyonlinelibrary.com exhibited much better ORR performances relative to P-C in terms of diffusion-limited current density, onset/half-wave potential and H 2 O 2 yields.…”
Section: Effect Of Transition Metals Acid Leaching and Second Pyrolymentioning
confidence: 66%
“…Energy Mater. [ 24 ] Li et al [ 129 ] 2 ] as N precursor) to prepare Fe X @NOMC (X: Fe mass content, NOMC: nitrogen-doped ordered mesoporous carbon). Nallathambi et al [ 218 ] made comparison on ORR activity of metal-free carbon support with and without metal-nitrogen chelate complex (Co-N, Fe-N, Co-Fe-N), showing that the carbon composite reached maximum activity with Co-Fe-N bound to the carbon support compared to Co-N and Fe-N complexes.…”
Section: Effect Of Transition Metals Acid Leaching and Second Pyrolymentioning
confidence: 99%
“…In this study, we used the templating method to obtain highly ordered mesoporous carbon with a high surface area. As these ILs are liquids at room temperature and show strong interactions with inorganic surfaces, they are ideal for use in nanocasting to generate nanostructures of highsurface-area N-doped carbons [11][12][13][14]. Since ILs tend to expand during heat treatment and ions without nitrile groups act as a porogen, it is difficult to obtain an ordered structure using a carbon replica of a hard template [11,14,16].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, ionic liquids (ILs) have been used in the synthesis of mesoporous carbons [10][11][12][13][14][15][16][17][18]. ILs exist in the liquid state at room temperature and exhibit negligible vapor pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is still challenge to develop an efficient method to synthesize the nitrogen-doped mesoporous carbon spheres with high surface area. Others' and our investigations indicated that the porosity and surface area are critical for mass transport and exposure of active sites of the ORR catalyst [50][51][52] . Others' and our investigations indicated that the porosity and surface area are critical for mass transport and exposure of active sites of the ORR catalyst [50][51][52] .…”
Section: Introductionmentioning
confidence: 99%